NEW INFLUENCES AND HIGHLIGHTS IN INSTRUCTIONAL DESIGN - Iasmina NEGRU; Simona SAVA (National Centre for Policy and Evaluation in Education, 2022)
Homework is a controversial topic that frequently attracts the attention of teachers and researchers, who are looking to identify ways to make it as attractive and enjoyable as possible, relevant, and formative as well. There are various points of views and data, empirically based, concerning the utility, scope, impact of homework on students' development. The aim of the study was to identify the reflections, perceptions, and stated practices of primary school teachers regarding the assignment and assessment of homework. Thus, 10 primary education teachers completed reflection diaries on homework, between May 26 and June 25, 2021 (a period of the schooling year with consolidations, evaluations, and gradual relaxation towards ending/summer holiday). The teachers were asked to record each two days their reflections. The coding of the entries in the reflection diaries was done and analyzed with MAXQDA, and it covered aspects like the purpose and role of homework, methods for effective assignment of homework, parental involvement, appropriate completion time, volume, etc. The results, informative for teachers and educational experts as well, reveal teachers' perceptions regarding the degree of involvement of children and parents, the appropriate dosage of effort and the appropriate time for solving homework, practices of assigning and evaluating students' homework.